Gene expression profile of normal and cancer‐associated fibroblasts according to intratumoral inflammatory cells phenotype from breast cancer tissue. Issue 11 (9th September 2015) - González, Lucía; Eiro, Noemi; Fernandez‐Garcia, Belen; González, Luis O.; Dominguez, Francisco; Vizoso, Francisco J.
Abstract : The biological heterogeneity of breast cancer leads to the need for finding new approaches to understand the mechanisms implicated in breast cancer progression. The tumor stroma appears as a key in the progression of solid tumors towards a malignant phenotype. Cancer associated fibroblasts (CAFs) may orchestrate a functional "corrupted" stroma which in turn helps metastatic spread. In this study, we investigated by real‐time PCR, the expression of 19 factors by normal breast‐associated fibroblasts (NAFs) and CAFs, which were implicated in several actions promoting tumor growth, such as extracellular matrix remodeling, inflammation and invasion. Also, we explored the influence of inflammatory cells phenotypes (MMP11 status) and breast cancer cell lines (MCF‐7 and MDA‐MB‐231) on the molecular profile of CAFs. If we consider that one of the major sources of CAFs are resident NAFs, the transition of NAFs into CAFs is associated with molecular changes involving the overexpression of some molecular factors of biological importance in tumor progression. In addition, the characterization of the tumor stroma regarding to the MMP11 status by MICs reflects a type of fibroblasts which contribute even more to tumor progression. Moreover, different patterns in the induction of the expression of factors by CAFs were observed, depending on the tumor cell line which they were co‐cultured with. Furthermore, CAFs influence TGFβ expression in both cancer cell lines. Therefore, this study can help to a better characterization of tumor stroma in order to improve the prognostic evaluation, as well as to define the different populations of CAFs as potential therapeutic targets in breast cancer. © 2015 Wiley Periodicals, Inc.